Asia-Pacific roadmap for primary forest conservation - Laumonier, Y.; Azzu, N.; Adzan, G.; Narulita, S.; Khikmah, F.; Meybeck, A.; Pingault, N.; Gitz, V. (CGIAR Research Program on Forests, Trees and Agroforestry, 2022)
Primary forests and natural landscapes in Asia and the Pacific are under increasing pressure and threats driven by population growth, migration and conflict, globalization and economic growth, urbanization, mining and infrastructure development, agriculture and planted forest expansion, forest fires and invasive species. Many of these threats are increasingly exacerbated by climate change. To address these threats, FAO and the Center for International Forestry Research (CIFOR), lead center of the CGIAR research programme on Forests, Trees and Agroforestry (FTA), have developed a roadmap for the conservation of primary forests in Asia and the Pacific, building upon state-of-the-art knowledge and extensive consultation of key regional stakeholders. This publication uses a remote-sensing methodology to accurately and consistently identify and delineate the remaining ‘intact forests’ and ‘contiguous intact forests’ in the Asia-Pacific region over large areas, over long periods of time, and at reasonable costs. It illustrates the huge diversity of forest formations in Asia and the Pacific and calls for a better understanding of the dynamic at stake in forest ecosystems and surrounding landscapes at finer scale. It proposes a set of recommendations, inviting policymakers and other relevant stakeholders to adopt an integrated landscape perspective and to combine different mechanisms and tools at different scales, including protected areas and other area-based conservation measures, to support effective primary forest conservation.